Koncept kontinuirane babiške skrbi: percepcija in vedenje nosečnic - Njenjić, Gordana (Obzornik zdravstvene nege, 2011)
Introduction: The concept of continuous care through pregnancy, labour and the early postnatal period in several European and world health systems offers advantages for both women and midwives. The pregnant women in Slovenia first encounter midwifery professionals in the delivery room whose expertise and competences thus remain only partially recognised. Methods: A descriptive research method was used in the present study. A questionnaire was based on the literature review of the relevant topic. The data were collected through an anonymous survey consisting of eight multiple choice closed-ended questions, six statements where the respondents specified their level of agreement or disagreement on a symmetric one to five agree-disagree Likert scale and three open-ended questions. Included in the study were 95 women in the third trimester of pregnancy who attended the antenatal courses for parents at the Gynecology Clinic of Ljubljana in April, 2010. A written consent was obtained from all the respondents. The data collected were analysed by a SPSS statistical software tool. Results: The respondents belonged to the following age groups: 21 to 30 years (over 50%), 31 to 40 years (40%) and over 40 years (approximately 3%). The sample group included 90 primiparas. 84% of the women agreed with the statement that midwives presentan autonomous professional group, 8% disagreed with the statement; 7% of the respondents were not familiar with the scope and competences of midwives. 82.1% were acquainted with their educational level. Only 24.2 of the respondents were familiar with the current position of midwifery practice within the health care system in Slovenia. 64.2% of the women were satisfied with the present womenćs health care as opposed to 35.8% who expressed their dissatisfaction. There was no statistically significant difference among the respondents as to the scope of practice among the age groups. Women with highest education would prefer being cared for by the same midwife throughout the entire treatment span (p = 0,017).
Keywords: babice; babištvo; Blennioidei; childbirth; human pregnancy; midwifery; nosečnost; porod